The role of APPRAISAL in the National Research Foundation (NRF) rating system evaluation and instruction in peer reviewer reports - Marshall, Christine Louise (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2010)
This thesis reports on two aspects of interpersonal meaning in peer reviewer reports for eleven researchers in the Animal and Veterinary Sciences awarded NRF ratings in A1, B1, C1 and Y1 rating categories. These aspects are the evaluation of the researcher applying for a rating, and the instruction to the NRF as to the rating the researcher ought to receive. A full APPRAISAL Analysis (Martin & White 2005) complemented by an investigation of politeness strategies (Myers 1989) is used to analyse the reports and show how the various systems of interpersonal meaning co-function and to what effect. The analysis reveals that there are clear differences between the evaluative and instructive language used in the reports. Those for the A1 rated researchers are characterised by only positive evaluations of the applicant, frequently strengthened in terms of Graduation and contracted in terms of Engagement. Overall there is less Engagement and politeness in these reports rendering them more 'factual' than the reports for the other rating categories. The A1 rated researcher is therefore construed as being, incontestably, a leader in his/her field of research, worthy of a top rating. The reports for the B1 and C1 rated researchers are characterised by the increasing presence of negative evaluations. In addition, there are more instances of softened/downscaled Graduation, dialogic expansion and deference politeness, showing that there is more perceived contention about the evaluations made. The reports for the Y1 rated researchers (a category for young researchers) focus on the applicant's demonstrated potential to become a leader in the field. In addition to a high incidence of negative evaluations, downscaled Graduation, dialogic expansion and deference politeness, the Y1 reports are also characterised by a high incidence of advice and suggestions from the reviewers concerning the applicant's work and standing. At a broader level, the analysis reveals that the language used in the reports has a profound influence on the outcome of the rating process. The reports are crucial, not only for evaluating the applicant but, also, more subtly, in directing the NRF towards a specific rating category. It offers insights into what is valued in the scientific community, what is considered quality research, and what leads to international recognition. The research also adds uniquely to current thinking about the language of science and, more particularly, highlights the nuanced understanding of evaluative and instructive language in the reports that is possible if one draws on the full APPRAISAL framework, and insights into politeness behaviour.
Keywords: Veterinary medicine -- Research -- Evaluation; Discourse analysis; Politeness (Linguistics); Accreditation (Education) -- South Africa; Quality assurance -- South Africa